Which patients with heart failure should receive specialist palliative care?. (28th June 2018) - Campbell, Ross T.; Petrie, Mark C.; Jackson, Colette E.; Jhund, Pardeep S.; Wright, Ann; Gardner, Roy S.; Sonecki, Piotr; Pozzi, Andrea; McSkimming, Paula; McConnachie, Alex; Finlay, Fiona; Davidson, Patricia; et al.
Abstract : Aims: We investigated which patients with heart failure (HF) should receive specialist palliative care (SPC) by first creating a definition of need for SPC in patients hospitalised with HF using patient‐reported outcome measures (PROMs) and then testing this definition using the outcome of days alive and out of hospital (DAOH). We also evaluated which baseline variables predicted need for SPC and whether those with this need received SPC. Methods and results: PROMs assessing quality of life (QoL), symptoms, and mood were administered at baseline and every 4 months. SPC need was defined as persistently severe impairment of any PROM without improvement (or severe impairment immediately preceding death). We then tested whether need for SPC, so defined, was reflected in DAOH, a measure which combines length of stay, days of hospital re‐admission, and days lost due to death. Of 272 patients recruited, 74 (27%) met the definition of SPC needs. These patients lived one third fewer DAOH than those without SPC need (and less than a quarter of QoL‐adjusted DAOH). A Kansas City Cardiomyopathy Questionnaire (KCCQ) summary score of <29 identified patients who subsequently had SPC needs (area under receiver operating characteristic curve 0.78). Twenty‐four per cent of patients with SPC needs actually received SPC ( n  = 18). Conclusions: A quarter of patients hospitalised with HF had a need for SPC and were identified by a low KCCQ score on admission. Those with SPC need spent many fewer DAOH and their DAOH were of significantly worse quality. Very few patients with SPC needs accessed SPC services.